ULANC - EUFOREA workshop 2024: bringing the concept of global airways to the frontline of medical care - D. M. Conti; D. M. Conti; V. Backer; K. Aanaes; A. Azizi; P. W. Hellings; P. W. Hellings; P. W. Hellings; S. Lau; G. Liva; G. K. Scadding; G. K. Scadding; et al. (Frontiers in Allergy, 2025)
The Upper and Lower Airways Northern European Consensus (ULANC) and the European Forum for Research and Education in Allergy and Airways diseases (EUFOREA) organized their first workshop in Copenhagen in January 2024. The aim of the “Primary care physicians and nurses with an interest in Global Airway Diseases 2024” was to bring the concept of the global airway to the front line of medical care. ULANC is a multidisciplinary European consortium, that aims to improve the management of comorbid ear, nose and throat (ENT) conditions, such as chronic rhinosinusitis with nasal polyposis (CRSwNP), in patients also suffering from asthma. EUFOREA is an international non-profit organization forming an alliance of all stakeholders dedicated to reducing the prevalence and burden of chronic respiratory diseases through the implementation of optimal patient care via educational, research, and advocacy activities. The inclusive and multidisciplinary approach of ULANC and EUFOREA was reflected in the keynote lectures and workshop faculty coming from the allergology, pulmonology, ENT, and primary health care fields around the central theme of global airway diseases. The current report aims at providing a comprehensive overview of the key statements by the faculty of the “Primary care physicians and nurses with interest in Global Airway Diseases 2024”, allowing all stakeholders in the respiratory field to be up-dated and ready to join forces in Europe and beyond.